2015
DOI: 10.1259/dmfr.20140343
|View full text |Cite
|
Sign up to set email alerts
|

Justification and good practice in using handheld portable dental X-ray equipment: a position paper prepared by the European Academy of DentoMaxilloFacial Radiology (EADMFR)

Abstract: Handheld portable X-ray devices are increasingly used for intraoral radiography. This development introduces new challenges to staff and patient safety, for which new or revised risk assessments must be made and acted upon prior to use. Major issues might be: difficulties in using rectangular collimation with beam aiming devices, more complex matching of exposure settings to the X-ray receptor used (e.g. longer exposure times), movements owing to the units' weight, protection of the operator and third persons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
33

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 10 publications
1
31
0
33
Order By: Relevance
“…There are no set of guidelines for duration of exposure, position -distance rule is not followed, radiation safety of operator is in question as the unit is handheld, and set angulations for exposures intraoral periapical radiographs cannot be met especially for lowers as the X-ray unit is obstructed by the patient's upper thorax and shoulders. The authors are in agreement Berkhout et al [10] for an international set guidelines for handheld digital X-ray.…”
Section: Discussionsupporting
confidence: 86%
“…There are no set of guidelines for duration of exposure, position -distance rule is not followed, radiation safety of operator is in question as the unit is handheld, and set angulations for exposures intraoral periapical radiographs cannot be met especially for lowers as the X-ray unit is obstructed by the patient's upper thorax and shoulders. The authors are in agreement Berkhout et al [10] for an international set guidelines for handheld digital X-ray.…”
Section: Discussionsupporting
confidence: 86%
“…Another recent study reported that occupational dose monitoring is highly recommended when aiming to secure continuous, low-radiation exposure using handheld X-ray devices. 21 Furthermore, handheld portable dental X-ray devices are not used routinely in dental practices in Europe; 22 however, this study showed that Korean dentists with less than 10 years of experience preferred to install handheld portable radiography devices in their practices (Table 4), but they were significantly less likely to monitor their occupational radiation exposures and attend the radiation safety program. Such attitudes may lead to decreased awareness of radiation protection procedures.…”
Section: Discussionmentioning
confidence: 76%
“…Such patients will likely require relevant imaging, and dental intraoral radiography has many advantages. With a mobile (or handheld) dental x-ray unit (Berkhout et al 2015), it can be performed on supine patients in hospital wards. Additionally, DPR and CBCT equipment usually requires the patient to stand or sit motionless for the duration of the exposure, which can be up to 40 s for some CBCT equipment (Nemtoi et al 2013).…”
Section: Letter To the Editormentioning
confidence: 99%